Total quality management, firm performance, and the moderating role of competitive intensity / Ramatu Abdulkareem Abubakar, Kabiru Maitama Kura and Kabiru Jinjiri Ringim - Abubakar, Ramatu Abdulkareem; Kura, Kabiru Maitama; Ringim, Kabiru Jinjiri (Universiti Teknologi MARA Cawangan Selangor, 2018)
By integrating resource-based view and theory of quality management we evaluated the moderating role of competitive intensity on the link between total quality management (TQM) implementation and SME performance. Using a stratified random sampling, 357 self-administered questionnaires were distributed to owner‐managers of SMEs operating in Kano and Kaduna in the north-west geopolitical zone of Nigeria. Of the 714 questionnaires distributed, 440 unusable questionnaires with 57 percent responses were returned and further analysed. The hypotheses were tested using Partial least squares structural equation modeling. Results supported the hypothesised main effect of TQM implementation on SME performance. However, our empirical study revealed that competitive intensity does not moderate positive relationship between TQM implementation and SME performance.